PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH - Syamsiah (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2020)
This study aims to analyze the effect of apparatus competence on Inspectorate audit quality in regional financial supervision, analyze the influence of apparatus independence on Inspectorate audit quality in regional financial supervision and simultaneously analyze the effect of competency and independence on Inspectorate apparatus audit quality in regional financial supervision at Rokan District Inspectorate Hulu. This research was conducted at the Rokan Hulu Regency Inspectorate. The data source of this research is employee respondents who work at the Inspectorate of Rokan Hulu Regency. with 32 respondents as research samples. Data analysis techniques in the form of descriptive statistical analysis, validity and reliability tests, normality tests, multicollinearity tests, Linearity Tests, and hypothesis tests (Determine Coefficient Test, T test and F Test). The results of this study are competence influential and significant on the audit quality of Rokan Hulu Regency Inspectorate Officers, but the direction is negative, Independence has a positive and significant effect on audit quality of the Rokan Hulu Regency Inspectorate Apparatus, and competence and independence influence on the audit quality of the Inspectorate Apparatus in regional financial supervision.